2016
DOI: 10.12659/msm.900954
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Factors Affecting Postoperative Axial Symptoms After Single-Door Cervical Laminoplasty for Cervical Spondylotic Myelopathy: A Prospective Comparative Study

Abstract: BackgroundPostoperative axial symptoms (post-AS) after single-door cervical laminoplasty for cervical spondylotic myelopathy (CSM) are a common and severe complication that adversely affects normal daily activities. Their etiology remains unclear. It is important to know which preoperative factors are the most predictive of post-AS. Therefore, this study aimed to elucidate the preoperative factors affecting post-AS.Material/MethodsA total of 102 patients with CSM who underwent single-door cervical laminoplasty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In recent years, there are extensive studies to explore the relationship among opening size, door shaft position, opening angle, sagittal canal diameter (SCD), spinal canal area and axial pain after SDCL [ 5 8 ]. However, most of the preoperative symptoms are caused by compression of the cervical spinal cord [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there are extensive studies to explore the relationship among opening size, door shaft position, opening angle, sagittal canal diameter (SCD), spinal canal area and axial pain after SDCL [ 5 8 ]. However, most of the preoperative symptoms are caused by compression of the cervical spinal cord [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Both open-door laminoplasty and laminectomy destroy the spinous process, vertebral plate, and posterior ligamentous complex to varying degrees, resulting in loss of effective attachment points for the posterior cervical muscles, weakening of the muscle tension band, and loss or straightening of cervical curvature. 6,7,10,12,13 A good physiologic curvature can result in a more elastic cervical spine, relieve shock, and buffer stress during movement, and therefore plays a role in protecting the spinal cord. 8 Borden et al 8 found that the normal cervical curvature is lordotic with cervical lordosis depth ranging between 7 and 17 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that destruction of the muscle-ligamentous complex and articular capsule, atrophy of the posterior cervical muscles, change of cervical curvature, and cervical instability are associated with AS development. 4,6,7,10,11,13 C5 palsy has been associated with multiple mechanisms such as ischemia and hypoxia, segmental spinal cord disorders, and embolism caused by increased nerve root tension. 5,14,19,20 Zhao et al 5 and Du et al 14 found that the incidence of postoperative C5 palsy significantly decreased with nerve root decompression, which reduces nerve root tension.…”
Section: Discussionmentioning
confidence: 99%
“…After intraoperative xation with lateral mass screws, the trend of progressive cervical curvature loss and high frequency of kyphosis deformities were effectively controlled, but the cervical curvature became smaller in some patients still existence [3,5]. From the analysis on anatomy and biomechanics, both open-door laminoplasty and laminectomy will destroy the spinous process, vertebral plate and posterior ligaments complex to varying degrees, resulting in loss of effective attachment points of the cervical posterior muscle group, weakening of the muscle tension band, loss or straightenness of curvature due to the failure to maintain the original cervical curvature [4,6,9,[11][12]. It has been reported that maintaining a good physiological curvature can make cervical spine more elastic, relieve shock and buffer stress during movement, and play a role in protecting the spinal cord [7].…”
Section: Discussionmentioning
confidence: 99%